Tracking Research on Hemoglobin-Based Oxygen Carriers: A Scientometric Analysis and In-Depth Review - Zhang Q; Ma YX; Dai Z; Zhang B; Liu SS; Li WX; Fu CQ; Wang QM; Yin W (Dove Medical Press, 2023)
Qi Zhang,* Yue-Xiang Ma,* Zheng Dai, Bin Zhang, Shan-Shou Liu, Wen-Xiu Li, Chuan-Qing Fu, Qian-Mei Wang, Wen Yin Department of Emergency, Xijing Hospital, Air Force Medical University, Xi'an, People's Republic of China*These authors contributed equally to this workCorrespondence: Wen Yin, Department of Emergency, Xijing Hospital, Air Force Medical University, No. 127 Changlexi Road, Xi'an, 710032, People's Republic of China, Email xjyyyw@fmmu.edu.cnAbstract: Numerous studies on the formulation and clinical applications of novel hemoglobin-based oxygen carriers (HBOCs) are reported in the scientific literature. However, there are fewer scientometric analysis related to HBOCs. Here, we illustrate recent studies on HBOCs using both a scientometric analysis approach and a scope review method. We used the former to investigate research on HBOCs from 1991 to 2022, exploring the current hotspots and research trends, and then we comprehensively analyzed the relationship between concepts based on the keyword analysis. The evolution of research fields, knowledge structures, and research topics in which HBOCs located are revealed by scientometric analysis. The elucidation of type, acting mechanism, potential clinical practice, and adverse effects of HBOCs helps to clarify the prospects of this biological agent. Scientometrics analyzed 1034 publications in this research field, and these findings provide a promising roadmap for further study.Keywords: blood substitutes, trauma, hemorrhagic shock, organ preservation, anemia, risk management